Zeeliedenstaking. Een sleperswagen en een grote verhuiskar onder militaire bewaking. Uit: Het Leven, 18-7-1911 (1911)
Zeeliedenstaking. Een sleperswagen en een grote verhuiskar onder militaire bewaking. Uit: Het Leven, 18-7-1911.